2014
DOI: 10.21804/17-1-739
|View full text |Cite
|
Sign up to set email alerts
|

New onset diabetes after transplantation in renal transplant recipients at Tygerberg Hospital

Abstract: New Onset Diabetes after Transplantation (NODAT) is a common complication of renal transplantation worldwide. However, there is very little data available regarding this condition in Sub-Saharan Africa. This study was therefore conducted in order to determine the incidence of NODAT and its associated risk factors in a South African renal transplant population. A retrospective analysis was conducted on 221 patients who underwent renal transplants at Tygerberg Hospital during the period January 1st 1995 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Similar results were observed in NODAT (39.3 ± 13.4) versus non-NODAT (33.9 ± 11.8) in Malaysian population. [33] Older age was observed as the risk factor for NODAT in populations of Brazil, [34] Turkey, [35] Portugal, [36] South Africa, [37] and Singapore. [38] Cosio et al [6] reported that there was 2.9 times increased risk in individuals undergoing renal transplantation, of age >45 years than younger patients.…”
Section: Discussionmentioning
confidence: 95%
“…Similar results were observed in NODAT (39.3 ± 13.4) versus non-NODAT (33.9 ± 11.8) in Malaysian population. [33] Older age was observed as the risk factor for NODAT in populations of Brazil, [34] Turkey, [35] Portugal, [36] South Africa, [37] and Singapore. [38] Cosio et al [6] reported that there was 2.9 times increased risk in individuals undergoing renal transplantation, of age >45 years than younger patients.…”
Section: Discussionmentioning
confidence: 95%